1038 Sleep Architecture In Individuals Receiving Methadone For Medication-Assisted Treatment Of Opioid Use Disorder. (27th May 2020) - Erwin, J A; Wilson, M; Finlay, M; Hansen, D A; Little-Gott, A; Reynolds, D; Quock, R M; Layton, M E; Van Dongen, H
Abstract: Introduction: It has been established that the use of opioids suppresses stage N3 sleep. For individuals with opioid use disorder (OUD), medication-assisted treatment (MAT) is a widely employed opioid replacement therapy used to mitigate withdrawal effects and drug cravings. We investigated sleep architecture in individuals receiving methadone-based MAT. Methods: N=6 individuals (aged 43.8±12.8y; 5 females), who were within 90 days of methadone initiation, underwent in-laboratory overnight polysomnography (8h TIB; 22:00-06:00). Prior to bedtime, pain intensity and opioid withdrawal symptoms were assessed using the Numeric Pain Rating Scale (0-10) and the Clinical Opiate Withdrawal Scale (0-48). Sleep recordings were scored visually according to AASM guidelines. Results: In this sample, subjects exhibited 87.4-93.0% (M: 92.2%) sleep efficiency (SE), 8.0-16.2min (M: 12.1min) sleep latency (SL), 5.5-7.5% (M: 6.5%) N1, 46.4-52.7% (M: 49.6%) N2, 20.7-30.6% (M: 25.6%) N3, 17.5-19.1% (M: 18.3%) REM, 28.0-38.5min (M: 33.3min) N3 latency, and 84.1-125.9min (M: 105.0min) REM latency. Subjects reported moderate pain intensity scores of 5-6 (M: 5.3) and mild to moderate withdrawal symptoms of 1-15 (M: 7.8). Conclusion: Relative to published healthy sleeper norms, subjects showed more N1 and N3 and less REM sleep. The increased N3 was unexpected given that opioids (such as methadone) typically suppress N3; it may reflect subjects carrying a substantial sleep debt. Pain and withdrawal symptoms may be a factor increasing N1 and reducing REM sleep. Such potential sleep deficiencies may interfere with subjects achieving OUD recovery goals and are worthy of further investigation. Support: Supported in part by a seed grant from the Washington State University Office of Research Advancement and Partnerships.